The Influence of Product Innovation, Consumer Awareness, and Environmental Policy on Sustainable Marketing in the Tourism Industry in Bali - I Wayan Jata (West Science Social and Humanities Studies, 2024)
This study explores the complex dynamics of sustainable marketing within Bali's tourism sector, emphasizing the influence of consumer awareness, product innovation, and environmental policy. The study uses Structural Equation Modeling with Partial Least Squares (SEM-PLS) to quantitatively analyze data from 245 varied participants in order to investigate the links between the major constructs. Psychometric qualities, demographic information, and descriptive statistics all support the measuring model's validity and dependability. The structural model coefficients show statistically significant positive correlations between Consumer Awareness, Environmental Policy, Product Innovation, and Sustainable Marketing. Discriminant validity analysis validates the distinctiveness of the components. The model has a significant explanatory power, as indicated by the R-Square values. In order to promote sustainability in Bali's tourism sector, firms, politicians, and researchers can benefit from the results' strategic insights.